Antioxidant capacity of Lemna gibba L. exposed to wastewater treatment - Karatas, Fikret; Obek, Erdal; Kamisli, Fethi (Elsevier Science Bv, 2009)
In this study, the amounts of antioxidant vitamins (A, E and C), selenium (Se), reduced glutathione (GSH)/oxidized glutathione (GSSG) ratio and malondialdehyde (MDA) that is the indicator of lipid peroxidation were determined in Lemna gibba L plants placed in the secondary clarifier and grown in natural water. The amounts of antioxidant vitamins (A, E and C) GSH, GSSG and MIDA were determined with HPLC (high performance liquid chromatography) and the amounts of Se were determined fluorimetrically. While significant decrease in amounts of antioxidant vitamins (A, E and C) and Se takes place between the first and the second or third day depending on species and insignificant decrease takes place after that day, the amount of GSH/GSSG ratio decreases until the second day (p < 0.05) and insignificantly increases after that day. Amounts of vitamins (A, E and C), Se and GSH/GSSG ratio for the plants placed in the secondary clarifier are much less than that for control group while an opposite trend was observed in MDA level. The MIDA for the plants placed in secondary clarifier has maximum value at the second day, which can be considered as the maximum stress occurring at that day. Consequently, the first two days of treatment time can be taken as acclimation time and after the acclimation time the plant lives in the hostile environmental condition with the certain amount of oxidative stress. As a result, it is determined that wastewater decreases the lifetime of plant by causing metabolic stress on it and affects antioxidant capacity. The lifetime of the plants in the secondary clarifier was determined to be five days since fading toward yellow color (necrosis) in the plants was observed at the fifth day. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Wastewater treatment; Lemna gibba L.; Vitamins; Selenium; Malondialdehyde; Glutathione